Adaptação transcultural e análise das características psicométricas de uma versão brasileira da escala de avaliação de anedonia Temporal Experience of Pleasure Scale (TEPS) - Rosar, Pedro Affonso (2019)
Objective: To propose a version of the Temporal Experience of Pleasure Scale (TEPS) for use in Brazil. Methods: Translation process, back translation, expert committee analysis according to established and internationally accepted criteria. Pre-test of the tool in a population of 40 adult individuals from a psychiatric outpatient clinic to adapt the applicability, maintaining the experimental and conceptual concepts of the scale. Subsequently, the scale had its psychometric characteristics tested on a population of 173 adult college students. The exploratory factorial analysis and extraction of the principal components by the Kaiser-Guttman method and rotated orthogonally by the Varimax method were performed. The internal consistency of the items was analyzed by the Cronbach's alpha coefficient. In addition, the intraclass correlation coefficient was estimated in a sample of approximately 20% of the population after the 7-day time period to evaluate the stability of the scale. The Hamilton Depression and Anxiety Scale (HADS) in its subset of depressive symptoms was used concurrent analysis. Results: The Cronbach's alpha coefficient of the proposed version of the TEPS scale was 0.745. The intraclass correlation coefficient in the test-retest was 0.815 (p <0.001). The analysis of the principal components revealed 3 factors responsible for explaining 43.5% of the variance, also shown in the Scree test. Depressive symptoms accessed through the HADS-d scale were poorly correlated. Conclusion: The proposed Brazil